Building Strong Leadership through Individual Concept in Leading Pesantren - Rusmini Rusmini; Erni Sukmawati; Indra Ruyani; Said Albukhari Alidrus; Said Muhammad Yusuf; Samsu Samsu (Dinasti Review, 2022)
Pesantren modern Shabilla Batam, Indonesia combines two different models of educational institutions, Pesantren combines Junior High School under the Ministry of Education with pesantren which is under the Ministry of Religious Affairs. This approach is supported by strong pesantren leadership. This study aims to examine the impact of personal conception in the formation of strong leadership to lead modern pesantren. The research method used is qualitative with a case study model. The research was conducted at Pesantren Modern Shabilla Batam with the subjects of the study being foundation leaders, pesantren caregivers, junior high school principals and teacher councils with a total number of participants of ten. The selection of participants was carried out by purposive method with the help of a key person. The data collection techniques used are interviews, observations and studies. The data obtained were analyzed using the Creswell (2015) approach model. The results showed a relationship between personal concepts and strong leadership. For this reason, it is recommended that research be carried out on many similar subjects to get a more complete picture.